Keberhasilan Pengobatan Tuberkulosis Paru dengan Komorbid Diabetes Mellitus di RSUD Al Ihsan Bandung Tahun 2020 - Rini Nur Islami Dinan; Julia Hartati; Heni Muflihah (Bandung Conference Series: Medical Science, 2023)
Abstract. Tuberculosis (TB) is an infectious disease caused by infection with the bacterium Mycobacterium tuberculosis. In TB patients with Diabetes Mellitus (DM), chronic hyperglycemia impairs immunity and causes prolonged treatment. The aim of this study was to analyze the relationship between DM comorbidities and the success of pulmonary TB treatment. This cross-sectional study used secondary data from the TB information system (SITB) and medical records. The subjects of this study were pulmonary TB patients undergoing treatment at Al Ihsan Hospital during 2020. The inclusion criteria included a minimum age of 19 years, pulmonary TB, and completion of treatment. Research data included TB DM status and treatment outcomes. The end result of complete treatment includes cured and complete. Total TB patients were 1319 people with adult pulmonary TB as many as 634 people who met the inclusion criteria. Most of the pulmonary TB patients were male, 360 people (56.78%) and adults (20-59 years) 455 people (71.77%). Pulmonary TB patients with comorbid DM were 12 people (1.89%) and 622 people without DM (98.11%). There are 10 out of 12 TB DM patients who have incomplete treatment outcomes. There is no relationship between DM comorbidities and the success of pulmonary TB treatment with a P value of 2.517 (P value > 0.05). The conclusion of this study is that there is no relationship between DM comorbidities and treatment success rates. Abstrak. Tuberkulosis (TB) adalah penyakit menular akibat infeksi bakteri Mycobacterium tuberculosis. Pada penderita TB dengan Diabetes Melitus (DM), hiperglikemia kronis merusak imunitas dan menyebabkan lamanya pengobatan.Tujuan penelitian ini menganalisis hubungan komorbid DM dengan keberhasilan pengobatan TB Paru. Penelitian cross sectional ini menggunakan data sekunder sistem informasi TB (SITB) dan rekam medik. Subjek penelitian ini adalah pasien TB paru yang menjalani pengobatan di RSUD Al Ihsan selama tahun 2020. Kriteria inklusi meliputi usia minimal 19 tahun, TB paru, dan menyelesaikan pengobaan. Data penelitian meliputi status TB DM and hasil akhir pengobatan. Hasil akhir pengobatn lengkap meliputi sembuh dan lengkap. Total pasien TB sebanyak 1319 orang dengan TB paru dewasa sebanyak 634 orang yg memenuhi krikteria inklusi. Sebagian besar pasien TB paru memiliki jenis kelamin laki-laki 360 orang (56.78%) dan usia dewasa (20-59 tahun) 455 orang (71.77%). Pasien TB paru dengan komorbid DM 12 orang (1.89%) dan tidak DM 622 orang (98.11%). Terdapat 10 dari 12 orang pasien TB DM memiliki hasil akhir pengobatan tidak lengkap. Tidak terdapat hubungan antara komorbid DM dengan keberhasilan pengobatan TB paru dengan P value 2.517 (P value > 0.05). Simpulan dari penelitian ini adalah tidak terdapat hubungan komorbid DM dengan angka keberhasilan pengobatan.